Intensified lipid-lowering treatment with alirocumab in patients with coronary heart disease. Issue 1 (17th May 2021) - Steffens, Daniel; Bramlage, Peter; Müller, Julia; Dorn, Cornelia; Paar, W Dieter; Scheeff, Celine; Kasner, Mario; Rauch-Kröhnert, U
Abstract : Background: Atherosclerotic cardiovascular disease is the leading cause of death and disability in the Western world. Objective: To characterise adults with confirmed coronary heart disease (CHD) and primary heterozygous familial or non-familial hypercholesterolaemia or mixed dyslipidaemia who received alirocumab in a real-world setting. Methods: This open, prospective, multicentre, non-interventional study, conducted in Germany, enroled patients with confirmed CHD who were treated with alirocumab according to its summary of product characteristics. Prescription was at the physician's discretion and independent of study participation. Patients were followed for 12 weeks after alirocumab initiation. Results: In total, 245 patients (mean age 62.2 years; 34.0% female) were documented at 90 sites. Overall, 47.7% had familial hypercholesterolaemia, 48.9% non-familial hypercholesterolaemia and 43.8% mixed dyslipidaemia; 74.6% had hypertension and 29.2% diabetes mellitus. The most common lipid-lowering therapy in the 12 months preceding alirocumab was a statin, often in combination with ezetimibe (73.5%). Statin contraindications were documented for 46.2% patients and statin intolerance for 63.8%. The mean low-density lipoprotein cholesterol (LDL-C)-level prior to alirocumab was 150.5±51.6 mg/dL. Alirocumab prescription was in compliance with German national recommendations and/or European guidelines. The most common starting dose was 75 mg every other week. Overall, 57% patients reached target LDL-C levels (<70 mg/dL) after 12 weeks of treatment. Alirocumab was generally well tolerated. Conclusion: In a real-world setting in Germany, alirocumab was prescribed for patients with atherosclerotic cardiovascular disease who had high baseline LDL-C levels with or without statin intolerance. Efficacy and safety were consistent with findings observed in the ODYSSEY Phase III programme.